2022
DOI: 10.1111/pan.14447
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the oropharyngeal leak pressure between three second generation supraglottic airway devices during laparoscopic surgery in pediatric patients

Abstract: Background Previous studies have shown Proseal LMA and I gel similar to endotracheal intubation in ventilatory ability in pediatric laparoscopic surgeries. Aims The primary aim of this study was to assess whether there is a significant difference in the oropharyngeal leak pressure between Ambu Auragrain, I‐gel, and Proseal LMA during pediatric laparoscopic surgery. Methods In this randomized controlled trial, 90 male patients of American Society of Anesthesiologists physical status I aged between 6 months and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A systematic review and meta-analysis of randomized controlled trials comparing SADs with ETTs was conducted by Bandyopadhyay et al They stated that for short pediatric laparoscopic procedures, the SAD could be an alternative to the ETT and reduced the incidence of postoperative sore throat and accelerated postoperative recovery [91]. In pediatric laparoscopic surgery, I-gel may be a better choice in cases of higher ventilation pressure [92]. However, a randomized controlled trial showed a higher likelihood of vocal cord injury when using I-gel compared to air-Q [93].…”
Section: Special Patientsmentioning
confidence: 99%
“…A systematic review and meta-analysis of randomized controlled trials comparing SADs with ETTs was conducted by Bandyopadhyay et al They stated that for short pediatric laparoscopic procedures, the SAD could be an alternative to the ETT and reduced the incidence of postoperative sore throat and accelerated postoperative recovery [91]. In pediatric laparoscopic surgery, I-gel may be a better choice in cases of higher ventilation pressure [92]. However, a randomized controlled trial showed a higher likelihood of vocal cord injury when using I-gel compared to air-Q [93].…”
Section: Special Patientsmentioning
confidence: 99%
“…3 However, supraglottic airway devices (SGAs) are being increasingly used for laparoscopic surgery in adult and pediatric surgical patients, with varying clinical performance characteristics. [4][5][6] SGAs have shown to offer several advantages over conventional tracheal intubation including improved intraoperative hemodynamic stability, reduced perioperative respiratory complications, decreased impairment of muco-ciliary clearance, and lesser requirement of anesthetics. 7 However, despite these potential benefits, the use of SGAs during pediatric laparoscopic surgery is not without problems.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, intubation with a tracheal tube (TT) and controlled ventilation is the gold standard for airway management strategy during general anesthesia for laparoscopic surgeries 3 . However, supraglottic airway devices (SGAs) are being increasingly used for laparoscopic surgery in adult and pediatric surgical patients, with varying clinical performance characteristics 4–6 . SGAs have shown to offer several advantages over conventional tracheal intubation including improved intraoperative hemodynamic stability, reduced perioperative respiratory complications, decreased impairment of muco‐ciliary clearance, and lesser requirement of anesthetics 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Supraglottic airways (SGAs) have been shown to be a safe alternative to endotracheal intubation in pediatric subumbilical laparoscopic surgical procedures (1)(2)(3)(4). Improvement of surgical conditions is also particularly important in pediatric laparoscopic surgery involving a SGA (4).…”
Section: Introductionmentioning
confidence: 99%